Low plasma lysophosphatidylcholines are associated with impaired mitochondrial oxidative capacity in adults in the Baltimore Longitudinal Study of Aging. Issue 2 (4th February 2019) - Semba, Richard D.; Zhang, Pingbo; Adelnia, Fatemeh; Sun, Kai; Gonzalez‐Freire, Marta; Salem, Norman; Brennan, Nicholas; Spencer, Richard G.; Fishbein, Kenneth; Khadeer, Mohammed; Shardell, Michelle; Moaddel, Ruin; et al.
Abstract: The decrease in skeletal muscle mitochondrial oxidative capacity with age adversely affects muscle strength and physical performance. Factors that are associated with this decrease have not been well characterized. Low plasma lysophosphatidylcholines (LPC), a major class of systemic bioactive lipids, are predictive of aging phenotypes such as cognitive impairment and decline of gait speed in older adults. Therefore, we tested the hypothesis that low plasma LPC are associated with impaired skeletal muscle mitochondrial oxidative capacity. Skeletal muscle mitochondrial oxidative capacity was measured using in vivo phosphorus magnetic resonance spectroscopy ( 31 P‐MRS) in 385 participants (256 women, 129 men), aged 24–97 years (mean 72.5) in the Baltimore Longitudinal Study of Aging. Postexercise recovery rate of phosphocreatine (PCr), k PCr, was used as a biomarker of mitochondrial oxidative capacity. Plasma LPC were measured using liquid chromatography–tandem mass spectrometry. Adults in the highest quartile of k PCr had higher plasma LPC 16:0 ( p = 0.04), 16:1 ( p = 0.004), 17:0 ( p = 0.01), 18:1 ( p = 0.0002), 18:2 ( p = 0.002), and 20:3 ( p = 0.0007), but not 18:0 ( p = 0.07), 20:4 ( p = 0.09) compared with those in the lower three quartiles in multivariable linear regression models adjusting for age, sex, and height. Multiple machine‐learning algorithms showed an area under the receiver operating characteristic curve of 0.638 (95% confidence interval, 0.554, 0.723) comparing six LPC in adults in the lower three quartiles of k PCr with the highest quartile. Low plasma LPC are associated with impaired mitochondrial oxidative capacity in adults.